Upaya Meningkatkan Minat Belajar Peserta Didik Melalui Permainan Berburu Binatang Dalam Pembelajaran PJOK di SMPN 28 Surabaya - Farhan Dwiki Mailiano Kumaat; Bambang Ferianto Tjahyo Kuntjoro; Ifanuddin Muchtar (Journal of Creative Student Research, 2024)
Comfort becomes very important when used as a driver to carry out learning that requires full concentration in receiving all materials. This factor also plays an important role in the success of learning. It can be seen from the comfort of each student. This classroom action research focuses on collecting information on how animal hunting games can increase students' interest in learning. This action was carried out in two cycles. The sample in this study was 30 students of class 9F SMPN 28 Surabaya. The results of the actions of cycle I and cycle II through observation and questionnaires were that there was an increase in students' interest in learning when using animal hunting games.